Nanobiotechnology in Agricultural Sector: Overview and Novel Applications - Alvarado, Katherine (2019)
The agricultural sector has many problems achieving the desired yield in products because of pathogens, viruses, pesticides, herbicides, temperature, soil moisture, among others. Nanotechnology, along with other sciences, has emerged in industry and society due to the interest in solving problems such as those mentioned above, in order to serve the needs of the world population. The present review discusses the principal topics about Nanobiotechnology, such as generalities, applications, aspects that can be improved and perspectives, beside its influence in the agriculture industry.